A importância do BalletPilates para o preparo físico da bailarina clássica - SOUZA, Amanda Almeida Vinente de (2018)
The present work deals with the Ballet and Pilates method and how the hybridity of these two practices contributed to the birth of BalletPilates. The research, carried out by the exploratory method of qualitative character, shows how this new method can help in improving the physical preparation of dancers, as demonstrated in practice. I still tell the story of Ballet, Pilates and BalletPilates, as well as describe the modules that make up their training: Fusion, Barreplus, Stick, Fitball, Aero and Fitafit. I emphasize that in the practical laboratories of BalletPilates, I worked only the Fusion module, with three dancers from Volé Cia. De Dança, because it is the basic module and prerequisite for the others. The result demonstrates the effectiveness of this new method in improving the fitness of dance practitioners.